Simulation of design parameters of a milking cup with an extended service life - Čėsna, J.; Medvedskyi, O.; Postol, Yulia; Kukharets, V.; Zayets, M.; Hrudovij, R.; Pantsyr, Yu.; Zarajczyk, J.; Zbigniew, D. (Sciendo : 2022, 2022)
EN: Modern milking machines need some additional studies to meet the requirements as to milking equipment. An imperfect design of a teatcup results in an incomplete milking of cows. The availability of devices for milk flow stimulation promotes an increase in a cow milk yielding capacity. But here arises a problem of an uncontrolled axial motion of a teatcup on a teat. As a result, a full milkflow is reduced, particularly at the final stages of milking. There is an effect of an increase in an inner diameter of a liner barrel, which causes that teatcups fall down. A scientific problem of the mitigation of some negative developments with the view to improve the efficiency of a teatcup arises. In a teatcup shell a liner is in a detended position during milking and resting periods. Thus, it under constant stretching. It results in a loss of elasticity irrespective of the material, as well as in reduction ofthe period of service maintenance. The use of a device for supporting a liner which is in a stretched state only during the milkflow, will result in an increase of a teatcup efficiency. The suggested automatic pneumatic mechanism releases a liner from the load during the resting period. The dependence of a tension force of a liner from the surface area of an annular membrane has been established. It has been proven that the membrane surface of 0.00065 m2 provides tension for a mechanism performance irrespective of operating vacuum pressure. The regression equation which connects geometrical parameters of an operating system with the efforts directed at the opening of a leading membrane has been received. A suitability of operation of using a pneumatic tightening device has been substantiated. An insignificant axial motion of a liner during a cycle of milking creates a stimulating effect. As a result, a completeness of miliking increases by 3-8%. PL: Współczesne maszyny udojowe wymagają prowadzenia dalszych badań, aby sprostać wymaganiom sprzętu udojowego. Nieidealny project kubka udojowego wpływa na niezupełny wydój krów. Dostępność urządzeń do stymulacji przepływu mleka zwiększa wydajność udoju. Jednak, pojawia się problem niekontrolowanego ruchu osiowego kubka udojowego na strzyku krowy. W rezultacie, przepływ mleka jest zmniejszony, szczególnie na końcowych etapach udoju. Dochodzi do zwiększenia wewnętrznej średnicy gumy strzykowej co powoduje odpadanie kubków udojowych. Pojawia się kwestia złagodzenia niektórych negatywnych skutków aby ulepszyć wydajność kubków udojowych. W kubku udojowym, guma strzykowa znajduje się w pozycji odprężenia podczas dojenia i spoczynku. Dlatego podlega ciągłemu rozciąganiu. Powoduje to zmniejszenie elastyczności bez względu na materiał a także skrócenie okresu serwisowego. Zastosowanie urządzenia do potrzymania gumy, która znajduje się w stanie rozciągnięcia tylko podczas przepływu mleka, spowoduje zwiększenie wydajności kubka udojowego. Zaproponowany automatyczny mechanizm pneumatyczny zwalnia gumę od obciążenia podczas okresu spoczynku. Ustalono zależność siły napięcia gumy od powierzchni membrany pierścieniowej. Udowodniono, że powierzchnia membrany 0.00065 m2 dostarcza napięcia mechanizmowi bez względu na podciśnienie robocze. Otrzymano równanie regresji, które łączy parametry geometryczne systemu roboczego z wysiłkiem skierowanym na otwarcie membrany. Potwierdzono odpowiedniość działania przy zastosowaniu pneumatycznego urządzenia zacieśniającego. Nieznaczący ruch osiowy gumy podczas dojenia stwarza efekt stymulujący. W rezultacie kompletność udoju zwiększa się o 3-8%.
Symulacja parametrów projektowych kubka udojowego o przedłużonej żywotności
Čėsna J., Medvedskyi O., Postol Y., Kukharets V., Zayets M., Hrudovij R., Pantsyr Yu., Zarajczyk J., Zbigniew D. Simulation of design parameters of a milking cup with an extended service life. Scientific Journal Agricultural Engineering. 2022. Vol. 26. No.1. PP. 243 -252.
Keywords: milking; teatcup; cow; milk; dojenie; kubek udojowy; krowa; mleko